2022
DOI: 10.15408/ijee.v9i1.23033
|View full text |Cite
|
Sign up to set email alerts
|

“Elsa Speak” in an Online Pronunciation Class: Students’ Voices

Abstract: Developing productive skills such as pronunciation requires more than just comprehension. Students should have ample opportunities to practice their knowledge. With the strike of Covid-19 that has abruptly shifted learning from offline to an online setting, lecturers have tried to employ technologies such as Elsa Speak in teaching pronunciation online. With the rising popularity of this application, there should be a study investigating how the students perceive Elsa Speak in online pronunciation learning. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The advancement observed in students' pronunciation skills is notably attributed to the app's capability of providing instant feedback, a feature widely acknowledged and appreciated by students. This aligns with Yosintha and Rekha (2022), where they highlight the app's effectiveness for pronunciation learning. ELSA Speak has everything students need to study pronunciation independently at their own pace and different levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The advancement observed in students' pronunciation skills is notably attributed to the app's capability of providing instant feedback, a feature widely acknowledged and appreciated by students. This aligns with Yosintha and Rekha (2022), where they highlight the app's effectiveness for pronunciation learning. ELSA Speak has everything students need to study pronunciation independently at their own pace and different levels.…”
Section: Discussionsupporting
confidence: 79%
“…The consequent enhancement of speaking capabilities, producing more coherent and error-free oral compositions, is a noteworthy accomplishment and valuable tool. As well as Dini et al ( 2021), cited in Yosintha and Rekha (2022), also found the distinct advantage of ELSA Speak's immediate feedback that can firmly affirm the significance of ELSA Speak in providing feedback to students for EFL classes at present times at any given moments. Furthermore, the enrichment of students' language competence and speaking comprehension via AI feedback validates the application of AI feedback in EFL speaking classes as a form of learning assistance from an empirical and theoretical standpoint.…”
Section: Discussionmentioning
confidence: 76%
“…The previous studied mostly focus on studying the use of commonly used applications, such as Youtube, Whatsapp, ELSA Speaks, Duolingo, etc. The results of research on ELT using the ELSA Speaks application explained that the majority of students expressed a favorable opinion of Elsa Speak, which was used in their online pronunciation class (Yosintha, 2022). Also Hamad et al (2019) argue that YouTube videos and Listening Audio Tracks Imitation are very effective CALL tools for improving students' speaking skills.…”
Section: Introductionmentioning
confidence: 99%